Planetary physics research programme at the Facility for Antiprotons and Ion Research at Darmstadt. Issue 10 (3rd November 2017) - Tahir, N.A.; Lomonosov, I.V.; Borm, B.; Piriz, A.R.; Neumayer, P.; Shutov, A.; Bagnoud, V.; Piriz, S.A
Abstract : Planetary physics research is an important part of the high energy density (HED) physics programme at the Facility for Antiprotons and Ion Research (FAIR) at Darmstadt. In this paper, we report numerical simulations of a proposed experiment namedLA boratoryPLA netaryS ciences (LAPLAS ). These simulations show that in such experiments, an Fe sample can be imploded to extreme physical conditions that are expected to exist in the interior of the Earth and in the interior of more massive rocky planets named, super‐Earths. The LAPLAS experiments will thus provide very valuable information on the equation‐of‐state (EOS) and transport properties of HED Fe, which will help the scientists to understand the structure and evolution of the planets in our solar system and of the extrasolar system planets.